Text Comprehension And roduction in University Students: Text Reformulation - Tittarelli, Ana María (2006)
This paper sets out to report on findings about features of task-specific reformulation observed in university students in the middle stretch of the Psychology degree course (N=58) and in a reference group of students from the degree courses in Modern Languages, Spanish and Library Studies (N=33) from the National University of La Plata (Argentina). Three types of reformulation were modeled: summary reformulation, comprehensive and productive reformulation.The study was based on a corpus of 621 reformulations rendered from different kinds of text. The versions obtained were categorised according to the following criteria: presence or absence of normative, morphosyntactic and semantic difficulties. Findings show that problems arise particularly with paraphrase and summary writing. Observation showed difficulties concerning punctuation, text cohesion and coherence , and semantic distortion or omission as regards extracting and/or substituting gist, with limited lexical resources and confusion as to suitability of style/register in writing. The findings in this study match those of earlier, more comprehensive research on the issue and report on problems experienced by a significant number of university students when interacting with both academic texts and others of a general nature. Moreover, they led to questions, on the one hand, as to the nature of such difficulties, which appear to be production-related problems and indirectly account for inadequate text comprehension, and on the other hand, as to the features of university tuition when it comes to text handling.